Need for criminal reform or legislative demagogy? Considerations on the circumstance of aggravation of the murder crime introduced by the Law 1696 of 2013 (2014)
This paper discusses how Colombian criminal law treats the perpetrator of a crime who is under the influence of alcohol or drugs. Specifically, the article analyzes the motivations behind the introduction of a new aggravating circumstance for involuntary